PRINSIP PERKAWINAN MENURUT HUKUM ISLAM DAN UNDANG-UNDANG NO.1/1974 (STUDY ANALISIS TENTANG MONOGAMI DAN POLIGAMI) - Ropiah, Siti (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2011)
The purpose of this paper to find out what the principles set forth in Islamic law and Law No. 1 of 1974 concerning marriage, and trying to put your about monogamy and polygamy are more proportional. From this paper can be concluded that the principle of marriage according to Islamic law is Monogamy with polygamy as an exception, based on the Qur'an Sura al-Nisa verse 3 and 129 which requires fair (justice). The principle of marriage according to Law No. 1 of 1974, under section 3 is open monogamy, which means a permissibility of polygamy on condition that certain conditions as article 4 of Law No.1/1974